Alcohol in the second half of life: do usual quantity and frequency of drinking to intoxication increase with increased drinking frequency?. (12th November 2014) - Brunborg, Geir Scott; Østhus, Ståle
Abstract Aims We investigated if increased drinking frequency among adults in the second half of life co‐occurred with increased usual quantity and increased intoxication frequency. Design Two‐wave panel study. Setting Norway. Participants Norwegian adults (1017 women and 959 men) aged 40–79 years. Measurements Drinking frequency, usual quantity and intoxication frequency was measured by self‐report in 2002/03 and again in 2007/08. Information about gender, age and level of education was obtained from the public register. Health was collected by self‐report. Findings Because of a significant gender × change in drinking frequency interaction effect on change in intoxication frequency (b = 0.02, P = 0.013), women and men were analysed separately. After adjusting for covariates, women who increase their drinking frequency showed a non‐significant decrease in usual quantity [low initial usual quantity (LIUQ): β = −0.01, P = 0.879; high initial usual quantity (HIUQ): β = −0.06, P = 0.164] and a non‐significant increase in intoxication frequency (LIUQ: β = 0.04, P = 0.569; HIUQ: β = 0.09, P = 0.251). Men who increased their drinking frequency showed a small decrease in usual quantity (LIUQ: β = −0.06, P = 0.049; HIUQ: β = −0.05, P = 0.002) and a small increase in intoxication frequency (LIUQ: β = 0.05, P = 0.035; HIUQ: β = 0.13, P = 0.004). Conclusion Among Norwegian adults in the second half of life, increased drinking frequency appears to be associated with a small reduction in usual quantity, and a small increase in frequency of drinking to intoxication.